Behavioural responses of Anodonta anatina and Unio pictorum to temperature and algal concentration. (21st December 2021) - Zapitis, Charitos; Huck, Maren; Mehra, Aradhana; Bulling, Mark T; Ramsey, Andrew
ABSTRACT: Using time-lapse photography in a laboratory setting, we exposed Anodonta anatina and Unio pictorum for 4 h to algal ( Chlorella vulgaris ) concentrations ranging from 0.5 to 20.0 mg ash-free dry mass l −1 and to three different temperatures (11 ± 1, 15 ± 1 and 19 ± 1 °C). We analysed the proportion of mussels in locomotion, duration of locomotory activities, posterior tip movement and valve opening behaviour. The proportion of mussels in locomotion was significantly higher for A. anatina and for A. anatina was significantly lower at 11 °C. For both species, the proportion of mussels in locomotion, the duration of locomotion and movement of the posterior tip decreased with increasing algal concentration. The locomotory duration was significantly shorter in U. pictorum . In both species, valve opening peaked at intermediate algal concentrations, with the deviation from the peak being more prominent in A. anatina . Finally, we recorded a contrasting locomotory strategy for the two species ( A. anatina crawled on the sediment surface, whereas U. pictorum moved through the sediment) and identified potential density dependence in behavioural adaptation.